Breast development in the newborn. Issue 7 (July 1981) - McKiernan, J F; Hull, D
Abstract : Breast size and milk secretion was studied in term and preterm infants. Breast nodules were palpable in most of the mature infants, both boys and girls. In 6 term infants without palpable breast tissue there was a high incidence of complications during late pregnancy or delivery. In light-for-gestational age infants the breast diameter was generally appropriate for gestation. None of the infants under 31 weeks' gestation had palpable breast tissue at birth, but some in the first weeks of life developed breast tissue and secreted milk. Milk had been secreted by most of the mature infants by age 7 days, and the onset was earlier in light-for-dates infants. The breast does not regress rapidly after birth. The nodules persist into the second half of the first year by which time sex differences have emerged. Clearly the growth and activity of the neonatal breast cannot be explained solely in terms of the influence of maternal hormones towards the end of gestation. Further studies on early breast tissue development may indicate the other endocrine factors concerned.